Advances in Radiation Therapy for Anal Cancer - Chiang, Jennifer S.; Rahimy, Elham (Digestive Disease Interventions, 2025)
Given its rarity and prognostic heterogeneity, improving outcomes for anal cancer can be challenging. Since the seminal Nigro study in the 1970s, chemoradiation has become standard of care, curing a large portion of patients and avoiding morbidity of an abdominoperineal resection. More advanced disease has a poorer prognosis and response rate. Radiation protocols, focusing on optimal dosing/fractionation and the integration of chemotherapy agents, are evolving. Modern techniques such as intensity-modulated radiation therapy have further reduced toxicities to improve patient outcomes. Despite these technological advancements, long-term toxicities, including bowel, urinary, and sexual dysfunction, remain significant issues. Ongoing clinical trials, such as the ACT II and PLATO trials, are redefining dose escalation and de-escalation protocols for both early- and late-stage tumors, balancing efficacy with quality of life. As we move toward personalized approaches to anal cancer treatment, this review highlights the importance of multidisciplinary care and ongoing research in optimizing chemoradiotherapy regimens, minimizing side effects, and enhancing survival outcomes for this challenging rare malignancy.
Keywords: anal squamous cell carcinoma; chemoradiotherapy; HPV-associated malignancy; quality of life; precision medicine